Recovery Policy Models on Usaha Mikro, Kecil dan Menengah (UMKM) Affected By Toll Road As A Solution To The Decrease Of Family Life Quality (Case study in the society of Kabupaten Serdang Bedagai Sumatera Utara) - Syafrizal Syafrizal (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
The purpose of this study is to explain the phenomenon of the policy model of regional heads in the recovery of UMKM affected by toll roads as a solution to the deterioration of quality of life, in the community of Serdang Bedagai Regency, as well as efforts to find alternative problem solving, related to social realities that occur in the community.The construction of Medan-TebingTinggi Toll Road, as an integral part of the overall national development, in the form of a series of activities that take place independently, but on the other hand its a part of something that is endless (never ending).The meaning of sustainable development, essentially aligning the benefits of natural resources and human resources in the form of progressive transformation of social, economic, political structures, to improve the welfare of society without sacrificing future generations.The research was conducted with qualitative approach by interactive method, with inductive data analysis. The results of the research were used as instruments to influence provincial-level government policies, as well as offer alternative solutions to problems that have occurred so far in the people of SerdangBedagai Regency.